PERAN DINAS SOSIAL DALAM PEMBERDAYAAN MASYARAKAT MISKIN DI KECAMATAN TAWALIAN - Rosmaida Rosmaida; Agustinus Sudi; Yusuf Daud (MITZAL (Demokrasi, Komunikasi dan Budaya) : Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2021)
This study aims to identify and describe the role of the Social Service in empowering the poor as well as the supporting and inhibiting factors in Tawalian District, Mamasa Regency. The method used is qualitative data analysis techniques. Data collection techniques used include observation, interviews (interviews), literature study, and documentation. The results of the study indicate that the role of the Social Service in empowering the poor in Tawalian District includes planning, data collection, and assistance has not been carried out properly. The impression is less than optimal due to lack of good coordination between local governments, data collection on recipients of the Family Hope Program (PKH) assistance that is not right on target. The supporting factors are the availability of the budget and the participation of community leaders, while the inhibiting factors are unprofessional data collection and limited human resources.